2018
DOI: 10.1145/3134842
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Trade-Based Edge Device Management in Multi-Gateway IoT

Abstract: The Internet-of-Things (IoT) envisions an infrastructure of ubiquitous networked smart devices offering advanced monitoring and control services. The current art in IoT architectures utilizes gateways to enable application-specific connectivity to IoT devices. In typical configurations, IoT gateways are shared among several IoT edge devices. Given the limited available bandwidth and processing capabilities of an IoT gateway, the service quality (SQ) of connected IoT edge devices must be adjusted over time not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…With the increasing number of IoT devices and services, security management of such devices is becoming an essential issue. Security management consists of all aspects of safety support for IoT devices, such as system monitoring, response capabilities, update policies, and asset management [99]. Current IoT stack architecture technology employs gateways (e.g., routers or hubs) to provide specific connectivity to IoT networks and other connected devices.…”
Section: ) Lack Of Security Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing number of IoT devices and services, security management of such devices is becoming an essential issue. Security management consists of all aspects of safety support for IoT devices, such as system monitoring, response capabilities, update policies, and asset management [99]. Current IoT stack architecture technology employs gateways (e.g., routers or hubs) to provide specific connectivity to IoT networks and other connected devices.…”
Section: ) Lack Of Security Managementmentioning
confidence: 99%
“…Blockchain-Based Schemes as Decentralized Security Controllers: Several studies have demonstrated the potential of utilizing blockchain to efficiently control and manage the authentication of devices, such as edge nodes, gateways, and other connected machines in IoT-based systems [200]- [203]. Conventional ASs for IoT applications [96], [97], [99], [109], [182] typically rely on a centralized server or certificate authorization center as a trusted third party; therefore, such systems are at risk of single-point failure [202]. However, in blockchain-based AS (a decentralized distributed system), encrypted blocks are performed on IoT devices as the sidechains that can be applied as a new strategy to support device authentication in IoT-based systems [203].…”
Section: A Open Problemsmentioning
confidence: 99%
“…It is expedient to realize the distributed computing with computational offloading to more powerful layers, such as heterogeneous fogs [4]. However, it requires data transmission over a gateway, where low power wireless connection and slightly large bandwidth allocation are the major issues [5]. sion algorithms [6] [7] [8] [9] at edge devices, but they are sometimes computationally intensive.…”
Section: Introductionmentioning
confidence: 99%